Ethical Issues In Academic Programs At Higher Institutions Of Learning In Malaysia: A Case Study Of Stamford College - Narayanasamy, Kogilah (2005)
The study on ethical values in academic programmes has caught the attention of many researchers througout the world. Many academic programmes today focus on how to make profit both for the individual and the organization and on how to increase the company's market share and shareholders value. Thus, this study is was undertaken to evaluate the extent of integration of ethical values in the academic programmes of one of the institution of higher learning operating in Malaysia namely Stamford College.